Faculty of philosophy and social sciences in my heart: 30 years of development and creation - Danilov, Alexander N.; Zelenkov, Anatoly I.; Rubanau, Anatoly V.; Bobr, Alexander M.; Liahchylin, Anatoli A.; Rotman, David G.; Tereschenko, Olga V. (Journal of the Belarusian State University. Sociology, 2019)
The round table is devoted to the 30th anniversary of the creation and work of the faculty of philosophy and economics, which was transformed into the faculty of philosophy and social sciences in 1999. The history of the faculty, departments, recruitment, stages of development are considered. The specialties, the main directions of development of the new faculty and the place of training humanities and social sciences in the national system of higher education, the specificity and relevance in society of these specialties are marked out. The modern ideas about the quality of knowledge are considered, special attention is paid to the practice-oriented nature of the preparation and implementation of the triad: education – science – practice. Attention is drawn to the need of developing a methodology for creative learning and updating the content of education in accordance with new challenges of the time. The future of the faculty of philosophy and social sciences is considered in the context of developing the national education system and its inclusion in the global educational context. The faculty members, deans of different years, heads of departments, teachers are invited.
Keywords: Belarusian State University; faculty of philosophy and economics; faculty of philosophy and social sciences; department of philosophy and methodology of science; department of sociology; department of social communication; history